2013
DOI: 10.1037/a0026913
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of big-five factors over the life span: ESEM tests of gender, age, plasticity, maturity, and la dolce vita effects.

Abstract: This substantive-methodological synergy applies evolving approaches to factor analysis to substantively important developmental issues of how five-factor-approach (FFA) personality measures vary with gender, age, and their interaction. Confirmatory factor analyses (CFAs) conducted at the item level often do not support a priori FFA structures, due in part to the overly restrictive assumptions of CFA models. Here we demonstrate that exploratory structural equation modeling (ESEM), an integration of CFA and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
310
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(352 citation statements)
references
References 108 publications
(264 reference statements)
33
310
2
7
Order By: Relevance
“…The results point to specific neural networks sub-serving the psychological mechanisms that control emotional behavior and may aid in informing us more thoroughly about how emotional traits and executive functions shape each other. While NATI and PACS may at first glance seem to be opposites, it is important to note that negative and positive affect are distinct constructs rather than extremes on the same scale (Rush and Hofer, 2014;Tellegen et al, 1999;Watson et al, 1999), and that neuroticism and extraversion are also distinct constructs rather than opposites (Marsh et al, 2013). Our results support the view that while NATI and PACS both draw on prefrontal, insular and striatal resources when amygdalar networks are queried, the resting-state functional connectivity patterns predicted by each factor are distinct.…”
Section: Accepted Manuscriptsupporting
confidence: 75%
“…The results point to specific neural networks sub-serving the psychological mechanisms that control emotional behavior and may aid in informing us more thoroughly about how emotional traits and executive functions shape each other. While NATI and PACS may at first glance seem to be opposites, it is important to note that negative and positive affect are distinct constructs rather than extremes on the same scale (Rush and Hofer, 2014;Tellegen et al, 1999;Watson et al, 1999), and that neuroticism and extraversion are also distinct constructs rather than opposites (Marsh et al, 2013). Our results support the view that while NATI and PACS both draw on prefrontal, insular and striatal resources when amygdalar networks are queried, the resting-state functional connectivity patterns predicted by each factor are distinct.…”
Section: Accepted Manuscriptsupporting
confidence: 75%
“…These studies have typically found that starting at about age 12 or 13, people tend to shift from a morning preference to more of an evening preference (Adan et al, 2012;Cavallera & Giudici, 2008). However, if indeed conscientiousness levels tend to be lower among this age group than among the age ranges sampled in our research, as Marsh et al's (2013) work suggests, we would likely find the same pattern of results as we have presented herein. Similar to most other studies in the time-of-day preference literature, our data were cross-sectional and self-report.…”
Section: Discussionsupporting
confidence: 79%
“…In the StudyResponse sample, conscientiousness had a point estimate of .0401 and a 99% confidence interval of .0102 to .0756. 4 Given Marsh et al's (2013) finding that conscientiousness may decline after about age 45 or 50, we tested for nonlinear relationships between age and conscientiousness. We were unable to detect any such relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Second, invariance of item thresholds/intercepts (scalar invariance) implies that differences between items' mean levels in the groups of responses considered can be explained in terms of differences at the latent factor mean levels. Hence, strong measurement invariance (metric plus scalar) provides a justification for the interpretation of response-group differences based on latent means (Marsh, et al, 2013). Only if scalar invariance is achieved can ODD scores be meaningfully compared across sexes/informants.…”
mentioning
confidence: 99%
“…As a starting point, configural invariance is supported when the same symptoms are used to classify a construct, implying that the pattern of zero and nonzero loadings is similar across groups. First, invariance of factor loadings (metric invariance or weak measurement invariance) implies that the constructs themselves are the same, and is particularly important both in terms of relating factors to other constructs for different groups with cross-sectional data and for evaluating patterns of relations among variables in the same group over time with longitudinal data (Marsh, Nagengast, & Morin, 2013). This means that the corresponding factors have the same meaning in the different groups, i.e., the strength of the relations between each symptom and its ODD dimension is the same for both sexes and/or for parents and teachers.…”
mentioning
confidence: 99%